PANDANGAN TOKOH AGAMA KOTA LANGSA TERHADAP PEMAKSAAN HUBUNGAN SEKSUAL - Nairazi, Faisal (IAIN Langsa, 2017)
Law No. 23 of 2004 on Elimination of Domestic Violence (PKDRT) is one form of government effort to eliminate violence in the family that most of the victims are women. Religious figures state that coercion of sexual intercourse with wife is not allowed in Islam although it is basically obligatory for the wife to serve the husband's request, but if it is not aroused to serve him, he may offer or suspend it. The factors causing the coercion of husband's sexual intercourse with wife are still the dominant patriarchal value in our society (values that prioritize the interests of men). Values that side with men which then form unwritten rules